Contextualizing Practical Knowledge in Early Modern Europe - Leemans, Annemie (CITCEM, 2020)
The topic of this book is practical knowledge in early modern Europe, interpreted widely as recipes containing art procedures or medical panaceas between 1400 and 1700. In this book, the 1) origin or creation, 2) transmission or dissemination, and 3) use or consumption are key subjects for understanding the place of practical knowledge in early modern European society. After a historiographical and theoretical approach, this book applies Deleuze and Guattari's rhizome metaphor to art technological literature. The first part ends with a study about medical practitioners and mediators who disseminate practical knowledge through the printing press. The second part of the book is entirely dedicated to the bookletA Very Proper Treatise (1573), using a microhistory approach to study it.